2006
DOI: 10.1021/ie0513550
|View full text |Cite
|
Sign up to set email alerts
|

Enriching PSA Cycle for the Production of Nitrogen from Air

Abstract: A novel 2-bed 4-step enriching pressure vacuum swing adsorption (PVSA) cycle was developed for the production of N2 from air, using an X-type zeolite, with the separation being equilibrium-driven. The four steps were low-pressure feed, countercurrent heavy product pressurization, countercurrent high-pressure heavy reflux, and cocurrent depressurization. The enriched heavy and light products (N2 and O2, respectively) were withdrawn from the system during the feed and heavy reflux steps, with both products being… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 8 publications
(19 reference statements)
0
21
0
Order By: Relevance
“…These two approaches are referred to as stripping PSA and enriching PSA, respectively. [6][7][8]11 The stripping PSA approach dominates the literature, whereas only a paucity of information is available on the enriching PSA approach. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] The enriching PSA approach first appeared in the literature in a 1982 patent by Wilson.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These two approaches are referred to as stripping PSA and enriching PSA, respectively. [6][7][8]11 The stripping PSA approach dominates the literature, whereas only a paucity of information is available on the enriching PSA approach. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] The enriching PSA approach first appeared in the literature in a 1982 patent by Wilson.…”
Section: Introductionmentioning
confidence: 99%
“…Hirose and co-workers [6][7][8] and also Ebner and Ritter 15,16 showed that the HR enriching PSA process is limited to producing a pure heavy component at less than 100% recovery, and that the DR enriching PSA process has no such limitation and, in principle, can perform the perfect separation of a binary gas mixture by producing two pure components each at 100% recovery. Although either variant of enriching PSA can be used to enrich a heavy gas at any concentration in the feed mixture, such as N 2 from air, 11 enriching PSA appears to have an innate ability to concentrate a trace component in a feed stream, such as Xe in air. [17][18][19] For example, Leavitt examined the enrichment of a low concentration of Ar in N 2 ; 13 Hirose and co-workers studied the enrichment of CO 2 in air; 6-8 they, along with Ritter and coworkers, studied the concentration of Xe in air; [17][18][19] finally, Ritter and co-workers studied the enrichment of a low concentration of ethane in N 2 .…”
Section: Introductionmentioning
confidence: 99%
“…The mass balance of ith component for the gas phase in the adsorption bed is presented through Eq. (17) [51,52]: Fig. 3 The overall mechanism of CO 2 chemical absorption process where q i in the above equations is described through LDF relation as follows:…”
Section: Mass Balancementioning
confidence: 99%
“…The demand for high nitrogen purity, over 99%, in a low and medium amount in the industrial sector has urged a lot of companies to produce nitrogen from atmospheric air by PSA process [8]. Zeolite X-type and perovskite-type ceramic were used as adsorbents instead of the CMS sieve for nitrogen separation from air at high pressure [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%